Earthquake and its Impacts on Education: Aftermath Nepal Quake 2015 - Bal Krishna Basnet (Foxton Books, 2020)
Although earthquakes themselves do not kill people, they highlight the critical importance of physical infrastructure resilience, safety measures and preparedness for natural disasters. Earthquakes are one of several environmental crises that can be categorized as a natural hazard/disaster. This study uses the qualitative method of research. The semi-structured interview with follow up questions among the educational actors like students, head/teachers, officials from the district education office and the local NGO staff working in the field of education before and immediately after the earthquake. The content analyses of curriculum of secondary level and textbooks of grade IX and X as well as field visit/observation were carried out during the study. The result and the conclusion of this study show that following the 2015 earthquake, the preparation of emergency bags helped children and their families gather essential items in a ready-to-go bag specifically designed for disaster situations. Simulation activities in schools helped prepare students for future disasters, and there were also many initiatives to reduce student and teacher trauma following the 2015 quake, including the development of a credited 5-hour teacher professional development (TPD) counselling programme. The inclusion of school disaster risk reduction (DRR) education in the curriculum and textbooks containing information on earthquakes, their cause, effects and preventive measures have now been disseminated in many languages including Nepali and English.